Petição e repetição: a violência da vítima - Garzon, Francisco Gomes de Almeida (2012)
This master s degree dissertation refers to a possibility of human subjectivity constitution through violence, excessive pathos. According to the position of Fundamental Psychopathology, pathos constitutes the human, in the measure that psychism is a reply to the incidence of pathos. Research was conducted whereof the clipping of a clinical case, considering the possibility of the violence to constitute symptomatic expression of pathos, either for the repetition of the pathogenic scene or through the way of the symptom. Facing the unbearable character of pathos excessive by definition - the capacity of complex symbolic creation, to suture the mark of the trauma, could remain disengaged. The present research is destined to investigate the possibility of considering the repetition of the violence suffered for the subject as being a symptom of this subject, as well as investigating ahead on the nature of this symptom towards the given nature of pathos, excessively terrifying. The clinical case that motivates the present research offers subsidies to think the question. We cogitate if the patient, in the observed case, offers himself to violence as in a species of sacrifice, writing repeatedly in his body a pledge, order of recognition, petition and repetition that informs and certifies the impossibility to deal with the uncommon violence of pathos that reached him. His acts, that victimize himself in repeated situations of violence practiced by the other (Other), would configure the impossibility towards symptom?